2005
DOI: 10.1021/ol052166g
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical Calculations of Conformationally Relevant 1H and 13C NMR Chemical Shifts of Calixarene Systems

Abstract: [graphs: see text] QM GIAO calculations of 13C and 1H chemical shift values of the ArCH2Ar group have been performed, using the hybrid DFT functional MPW1PW91 and the 6-31G(d,p) basis set, on some representative calixarenes and on a series of simplified calixarene models allowing derivation of chemical shift surfaces versus phi and chi dihedral angles. A good reproduction of experimental data was obtained. The applicability of chemical shift surfaces in the study of calixarene conformational features is illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…As shown in Figure 1, the Scheme 1. [9] Moreover, we also found that only four signals due to the aliphatic carbons were observed in the 13 C NMR spectra of 4 b and 5 b. Scheme 2.…”
Section: Resultsmentioning
confidence: 71%
“…As shown in Figure 1, the Scheme 1. [9] Moreover, we also found that only four signals due to the aliphatic carbons were observed in the 13 C NMR spectra of 4 b and 5 b. Scheme 2.…”
Section: Resultsmentioning
confidence: 71%
“…In particular, an approach based on integrated NMR experimental data with GIAO 1 H NMR DFT calculated values was proposed to study ligand-macromolecule interactions, going well over the successful application of 1 H and 13 C NMR chemical shift calculations in the structure elucidation of organic molecules, [8a,9b,28] in the interpretation of polymer spectra [28d] and in the conformational analysis of peptides, [91][92][93] oligosaccharides, [94] and calixarenes. [95] Thus, two 3D models were built where 36 was covalently bound to A5 or A6 (model A or B, respectively; Figure 11a,b), and starting from the NMR structure of duocarmycin SA covalently linked to the DNA duplex (PDB [96] archive code 1DSA) [97] 36 was built and docked in the minor groove. [24] In order to perform quantum mechanical calculations in a reasonable computation time and with a reliable model, only six base pairs of the DNA were considered (Figure 11).…”
Section: Quantum Mechanical Calculation Of Nmr Parameters As a Tool Fmentioning
confidence: 99%
“…These properties make DFT more practical and feasible for the computations of large molecules and databases containing a sizable number of molecules. Accordingly, DFT methods are employed in most cases, and the methods unarguably provide the best compromise between computational cost and reliability among all quantum chemical methods . Moreover, there are different kinds of functionals for solving problems in different situations (molecular groups).…”
Section: Introductionmentioning
confidence: 99%